1999
DOI: 10.1074/jbc.274.46.32733
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer from Histidine 244 May Facilitate the 1,2 Rearrangement Reaction in Coenzyme B12-dependent Methylmalonyl-CoA Mutase

Abstract: Methylmalonyl-CoA mutase is an adenosylcobalamindependent enzyme that catalyzes the 1,2 rearrangement of methylmalonyl-CoA to succinyl-CoA. This reaction results in the interchange of a carbonyl-CoA group and a hydrogen atom on vicinal carbons. The crystal structure of the enzyme reveals the presence of an aromatic cluster of residues in the active site that includes His-244, Tyr-243, and Tyr-89 in the large subunit. Of these, His-244 is within hydrogen bonding distance to the carbonyl oxygen of the carbonyl-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 32 publications
6
53
0
Order By: Relevance
“…The steady formation of OH 2 Cbl during IcmF turnover under aerobic conditions suggests that inactivation might result from oxidative interception of cob(II)alamin (27). An alternative possibility is that inactivation is associated with loss of 5Ј-de- oxyadenosine from the active site, and the uncoupled cob(II)alamin is subsequently oxidized to OH 2 Cbl.…”
Section: Loss Of 5ј-deoxyadenosine Leads To Inactivation Of Icmf-mentioning
confidence: 95%
“…The steady formation of OH 2 Cbl during IcmF turnover under aerobic conditions suggests that inactivation might result from oxidative interception of cob(II)alamin (27). An alternative possibility is that inactivation is associated with loss of 5Ј-de- oxyadenosine from the active site, and the uncoupled cob(II)alamin is subsequently oxidized to OH 2 Cbl.…”
Section: Loss Of 5ј-deoxyadenosine Leads To Inactivation Of Icmf-mentioning
confidence: 95%
“…Previous workers studying the Propionibacterium shermanii enzyme have shown that at ambient oxygen concentrations (ϳ200 M), oxygen reacts with the Cbl(II) generated during the enzymatic reaction, albeit at a slow rate (40). Other workers found no inhibition of the P. shermanii enzyme under ambient conditions, but enzyme activity was measured over only a 3-min interval (41). We found that at 200 M, oxygen had a small but statistically non-significant effect on the activity of mammalian methylmalonyl-CoA mutase during a 10-min incubation, but at 600 M oxygen significantly inhibited enzyme activity (Fig.…”
Section: Effect Of Oxygen On Methylmalonyl-coa Mutase Activity In Vitromentioning
confidence: 95%
“…However, this may not apply to non-polar diatomic molecules like oxygen or NO, as oxygen has been shown to react with Cbl(II) generated by the P. shermanii enzyme, albeit at a slow rate (40). Mutation of the P. shermanii mutase at histidine 244 markedly increases the sensitivity of the enzyme to oxygen, indicating that this residue is critical for protecting the Cbl(II) and deoxyadenosyl radical intermediates (40,41). Modeling the possible structure of the homodimeric human enzyme against the known structure of the heterodimeric P. shermanii enzyme using the Swiss Model program suggests that the active sites of the two enzymes are similar, but such modeling can overlook subtle structural differences that could lead to increased sensitivity to NO and oxygen (52).…”
Section: Effect Of Decreased Availability Of Endogenous No On Methylmmentioning
confidence: 99%
“…computational studies on methylmalonyl-CoA mutase have begun to provide insights into these issues (3)(4)(5)(6)(7)(8). They point to the critical role played by individual active site residues in labilizing the Co-carbon bond (7), and in shielding radical intermediates from unwanted side-reactions (4,6,8).…”
mentioning
confidence: 99%
“…They point to the critical role played by individual active site residues in labilizing the Co-carbon bond (7), and in shielding radical intermediates from unwanted side-reactions (4,6,8).…”
mentioning
confidence: 99%